2021
DOI: 10.3389/fonc.2021.636373
|View full text |Cite
|
Sign up to set email alerts
|

Dual Inhibition of Ornithine Decarboxylase and A1 Adenosine Receptor Efficiently Suppresses Breast Tumor Cells

Abstract: Personized treatment of breast cancer is still a challenge, and more treatment options for breast cancer are warranted. Combination therapies have been a highly appreciated strategy for breast cancer treatment in recent years, and the development of new combination therapies could improve patient outcomes. Adenosine and polyamines are both endogenous metabolites with indispensable biological functions. Adenosine binds with the A1 adenosine receptor (A1AR) to downregulate cAMP concentration, and both low cAMP c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…55 Moreover, preclinical observations showed that hA 1 AR blockade by DPCPX inhibits cancer cell proliferation and promotes cell apoptosis. 15,56,57 Mutant receptors with altered receptorligand interaction, for example N148S EL2 , V152L EL2 , and M177V 5.35 in this study, may thus result in mis-dosing while using these small molecules as therapeutic approaches. Studies on GPCR heteromers provided evidence for the presence of hA 1 AR.…”
Section: Potential Role For Ha 1 Ar Mutations In Cancermentioning
confidence: 86%
“…55 Moreover, preclinical observations showed that hA 1 AR blockade by DPCPX inhibits cancer cell proliferation and promotes cell apoptosis. 15,56,57 Mutant receptors with altered receptorligand interaction, for example N148S EL2 , V152L EL2 , and M177V 5.35 in this study, may thus result in mis-dosing while using these small molecules as therapeutic approaches. Studies on GPCR heteromers provided evidence for the presence of hA 1 AR.…”
Section: Potential Role For Ha 1 Ar Mutations In Cancermentioning
confidence: 86%
“…The combined use of therapeutic agents within combination therapy has proven to be advantageous (over monotherapy) in several ways, such as enhanced efficacy, reduced side effects, and minimal drug resistance. Of clinical importance, several cancers have been reported to optimize this therapeutic approach, such as renal cell carcinoma, melanoma, Hodgkin’s lymphoma, and breast cancer to name a few ( 31 34 ). In particular, non-small cell lung cancer (NSCLC) is one of the prominent cancers where a number of studies documenting the clinical outcomes of mono and/or combination therapies have been reported ( ).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies in genetic mouse models of KRAS mutant pancreatic cancer showed the potential of using DFMO as a chemoprevention agent [20]. Additionally, DFMO has shown preclinical success in various cancer models [16,17,[23][24][25][26]. Most notably, DFMO has been successfully used in multiple clinical trials to treat neuroblastoma [16,17,27].…”
Section: Discussionmentioning
confidence: 99%